(untitled) (Research, Society and Development, 2021)
The bacteria are organized in an aggregated form in an extracellular matrix, called biofilm, a structure that gives protection to the bacteria, the action of antimicrobials and the hosts immune response. Therefore, Pseudomonas aeruginosa, is classified as an opportunistic microorganism, responsible for causing high numbers of nosocomial infections due to bacterial resistance developed by virulence factors such as biofilm, controlled by the quorum sensing system. Thereby, the objective of this work was to describe the communication of bacterial cells for the formation of biofilm by P. aeruginosa, during the process of colonization and infection in the host. This was followed by the methodology of a narrative review, based on articles published between 1990 and 2020, indexed in the Biblioteca Virtual em Saúde (BVS), using the descriptors: “quorum sensing”, "Pseudomonas aeruginosa", "biofilm", "virulence factors", "Flagella", "pili", "bacterial adhesion" "polysaccharide" "adhesins" and "biofilm matrix". Articles published in full, in English, between 2000 and 2020 were selected Incomplete articles, duplicates and academic papers such as theses and dissertations were excluded. The studies demonstrated that the bacterial resistance of P. aeruginosa to antibiotics is related to its high capacity to adapt to hostile environments and to the resistance mechanisms developed by the species, especially the formation of bacterial biofilm by the quorum sensing system from the biosynthesis of self-inducing molecules such as: N-3-oxo-dodecanoyl homoserine lactone, N-butanoyl-homoserin lactone and 2-heptyl-3-hydroxy-4-chi nolona, ​​responsible for mediating the production of virulence factors. This review addressed the general aspects involving the pathogenicity arising from bacterial communication during its colonization process.